Problematika Jilbab dalam Perspektif Quraish Shihab - Muhammad, Wildan Imaduddin (ISLAMITSCH FAMILIERECHT JOURNAL, 2020)
This paper attempt to explain how Quraish Shihab’s argument on veil. In his books entitled Jilbab, the controversy emerges among Muslim in Indonesia. I argue that Quraish Shihab’s argument of veiling is based on Muslim scholars along classical period until now. There is no prohibition or suggestion specifically about the rule of veil. Quraish Shihab position himself as Muslim scholar who expose the whole argument that he believes its true.